Influence of Cadmium-Sulphur Interaction on Growth and Nutrient Concentration of Wheat ,(TRITICUMAESTIVUM L.) in Aridisols - Gupta, V K; Mehta, D S (Annals of Arid Zone, 2016)
Investigations carried out in screen. house to study the influence of 0, 20, 40, 60, 80 and 120ug S/g soil; and 0, 5, 10.20,40 and 80ug Cd/g soil on growth and nutrient concentration of wheat was investigated in screen house. Cadmium application’ repressed and S improved wheat dry matter yield. The depressing effect of Cd on shoot dry matter yield was alleviated by S application. Addition of Cd decreased P, K, Cu, Mn and Zn concentration and enhanced Fe content in wheat shoot. Sulphur application markedly improved P,K, Mn, Cu and Fe concentration but decreased Zn concentration.